Shipping water across the us–mexico border: international governance dimensions of desalination for export - Mumme, S. P., McEvoy, J., Pineda, N., Wilder, M. (My University, 2017)
New public&ndashprivate desalination projects along the Mexico&ndashUnited States boundary have the potential to strengthen water security in this arid region. International bulk water commerce in this region is unprecedented and constrained by existing international agreements and regulations. This problem is examined from a multilevel governance perspective, focusing on two desalination projects with near-term export potential in Rosarito, Baja California, and Puerto Peñasco, Sonora. These projects add to the array of agencies and procedures in binational water management but will not displace the International Boundary and Water Commission, which is sure to have a role in managing such projects.
Keywords: Water export, desalination, NAFTA, IBWC, Colorado River, United States-Mexico border